THE OCCURRENCE OF ARTIFICIAL SURFACTANTS IN WASTEWATER AND THEIR CLEANING EFFICIENCY (The New Uzbekistan Journal of Medicine, 2025)
This article studies the occurrence of artificial surfactants (SUS) in wastewater and their cleaning efficiency. SUS, which have been widely used in industry since the 50s and 60s, are still actively used in production and domestic sectors today. They differ in their specific physicochemical properties in the aquatic environment and have a negative impact on the environment. The study analyzes the occurrence of SUS in wastewater, their sources and the level of loss in treatment facilities. The effectiveness of existing treatment technologies is also evaluated and proposals are developed to ensure environmental safety.